Contralateral reexpansion pulmonary edema with ipsilateral collapsed lung after pleural effusion drainage: a case report - Kim, Jae Jun (J Cardiothorac Surg, 2015)
Reexpansion pulmonary edema is a rare but potentially life-threatening condition that occurs when a collapsed lung reexpands, usually in the same side of collapsed lung. We present a rare case in which a 57-year-old Korean man had a large amount of malignant pleural effusion. After undergoing tube thoracostomy drainage for the pleural effusion, a contralateral reexpansion pulmonary edema developed while the ipsilateral lung was half collapsed. The patient was dyspneic with an oxygen saturation that dropped to 66 %. After conservative treatment with oxygen therapy, steroid administration, and negative suction application (suction pressure of -20 cm H(2)O) in the right pleural cavity for five days, the right lung could be fully expanded without development of reexpansion pulmonary edema, and the reexpansion pulmonary edema in the left lung resolved. Although it is a very rare condition, it is important to know that contralateral occurrence of reexpansion pulmonary edema can occur, especially when the ipsilateral lung is collapsed. Being aware of this potential condition can allow for early and proper management.